The Influence of Class Management and Teacher's Work Ethic on the Effectiveness of Learning at the Samarinda City Vocational High School - Warman Warman; Harliansyah Harliansyah; Lukman Priyandono; Lorensius Amon (Budapest International Research and Critics University, 2021)
This study is a quantitative study with the aim of knowing the effect of classroom management and teacher work ethic on the effectiveness of the teaching and learning process in Vocational High Schools in Samarinda City. The results of this study indicate that there is a positive and significant influence between classroom management and the effectiveness of the teaching and learning process. This is indicated by a correlation of 0.616 and interpretation if there is no Class Management then the effectiveness of the teaching and learning process is 95.120. Every one point increase in class management will increase the effectiveness of the teaching and learning process by 0.232 (significantly). Then, there is a significant and positive influence between the teacher's work ethic and the effectiveness of the teaching and learning process. This is indicated by a correlation of 0.107 and interpretation if there is no teacher's work ethic then the effectiveness of the teaching and learning process is 25,834. Every one point increase in the teacher's work ethic will increase the effectiveness of the teaching and learning process by 0.232 (Significant). Furthermore, there is a significant and positive effect between classroom management and teacher work ethic together with the effectiveness of the teaching and learning process in schools with a correlation of 0.713 with an interpretation of 71% that the teaching and learning process in SMK (Y) is influenced by class management (X1) and teacher's work ethic (X2), while the remaining 29% is influenced by other factors.